Examining the factors that influence the voluntary disclosure of information by consumers to commercial organisations - Themistocleous, Christos (My University, 2016)
The impetus of this research is to examine how different presentation techniques of data-capturing questionnaires influence the amount of voluntary disclosures of private information by consumers to commercial organisations. The research focused on the interaction of three dimensions that influence voluntary disclosures namely psychological processes, relational depth and instrumental factors, specifically utilising the three concepts deriving from the instrumental factors dimension for the synthesis of the questionnaires. These concepts were comparative nature (Acquisti, John and Lowenstein, 2012) dyadic relationships (Zimmer et al., 2010), and question sequences (Moon, 2000; Acquisti, John and Lowenstein, 2012). This research incorporated a 3x3x3 matrix based on the three respective conditions of the above concepts, thereby generating 27 different conditions -each of which reflected a unique presentation of the questionnaire. A quasi-experimental survey- based design was incorporated for the testing of each of these conditions and their influence towards three areas: i) Overall actual disclosure of information, ii) perceptions of individuals regarding loss of face, loss of privacy and compensation required for full disclosure, iii) perceptions of individuals regarding impersonal trust and subsequent relational depth. This examination was based on the conceptualisation of a three-dimensional framework which incorporated multidisciplinary factors identified by previous literature to have an influence on voluntary disclosure. Additionally, a pre-test study was utilised for identifying reliable measurements of overall actual disclosure while informing the design of the questionnaire based on the question sequence concept. This approach represents the first attempt at examining the synergistic behaviour of concepts that influence the presentation of data-capturing questionnaires; their comparison with the individual employment of each concept in terms of their influence on overall actual disclosure; as well as the examination of how each of these conditions influences the cognitive processes of individuals that lead them to disclosures of private information. This approach was complemented by analyses that sought to confirm the high-level conditions of each concept (H1), while deductively verifying previous claims by other academics and building upon their work (H3). Results provided confirmation of certain synergistic behaviours of concepts that increase overall actual disclosure, while pinpointing specific combinations that lead to abstention from information disclosures. Certain counterintuitive findings were also present and were addressed through a closer examination of previous research and a cross-examination of this Thesis’ hypotheses.
Keywords: Consumer Behaviour; Information disclosure; Consumer Privacy; Marketing; Καταναλωτικη συμπεριφορα; Αποκάλυψη προσωπικών πληροφοριών; Ιδιωτικότητα καταναλωτών; Μαρκετινγκ